Risk Assessment in Road Transport - Tumielewicz, Michał; Szmelcuch, Dominik (Towards Sustainable Transport in Logistics and International Trade, 2025)
The objective of the chapter is to identify and characterize risks occurring in road transport within the TSL sector and to assess the preventive measures undertaken by companies. A diagnostic survey was used, in the form of a questionnaire directed at employees in the TSL industry, enabling the collection of both qualitative and quantitative data. The results show that the most frequent risks include delivery delays, cargo damage, and road accidents. The main risk factors are a lack of driver skills, poor vehicle technical condition, and inadequate cargo securing. A limitation of the study is the relatively small number of respondents. Practical implications include the need for training, fleet modernization, and investment in road infrastructure. The social relevance of the research is tied to improving road safety. The value of the chapter lies in highlighting effective methods for minimizing risk and developing a road transport safety management system.